HUBUNGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET Fe DENGAN KEJADIAN ANEMIA : LITERATURE REVIEW - Angela Naingalis; Odilia Esem (Jurnal Maternitas Kebidanan, 2023)
Anemia in pregnancy is an indirect cause of death for pregnant women in Indonesia. Consumption of Fe tablets during pregnancy is an effort to prevent anemia. The purpose of this study was to provide an overview of the relationship between adherence to consuming Fe tablets and the incidence of anemia. The method used is literature review. Journal search sources in this study used the Garuda Portal and Google Scholar from 2015-2023 with the keywords used were pregnant women, consumption of fe tablets, anemia. Based on 5 articles about the relationship between adherence to consuming Fe tablets and the incidence of anemia, it was found that there was a significant influence between adherence to consuming Fe tablets and the incidence of anemia in pregnant women. The conclusion of this review of the literature review was that there was a significant influence between the adherence of pregnant women consuming Fe tablets to the incidence of anemia.